History over a century of the people, discoveries, disaters, and political and cultural events that rocked the world - Jackson, Bianca; Morton, Jonathan (Cassell Illustrated Sterling Publishing, 2008)
Talks about the people, events, ideas, battles and moments that, like King and his beliefs, rocked twentieth-century history. This book charts the most significant historical, social, political and cultural moments, and places each event, person, movement and idea in context to provide a comprehensive understanding of a century of world history.